Implementation of the Muhadatsah Method in Arabic Language Learning - fathiyah; Azhari, Saefullah; Jannah, Ida Miftahul (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2024)
This study aims to analyze the implementation of the muha>das|ah method applied in Arabic language learning in MAN Surabaya City. The research method used is qualitative with a descriptive approach. Data was obtained from two sources, namely primary and secondary with documentation, observation and interview techniques, then validity tests and conclusions were drawn. The results of the study show that the learning curriculum at MAN Surabaya City can be said to have succeeded in producing people who are fluent in Arabic, judging from the books used. The researcher also found that the students were very enthusiastic in participating in muha>das|ah activities using dialogue memorization techniques. The students were very enthusiastic about practicing dialogue in front of the class. The students were happy when they performed with their colleagues who were practicing dialogue using Arabic. By repeating it many times by the teacher and then followed by the students so that students can memorize and get used to the pronunciation faster.